Prior experiences of the new entrants in using the school library: with special reference to Management students, University of Peradeniya - Wijetunge, Pradeepa; Gunasekera, Chamani (My University, 2015)
The objectives of the study was to examine the previous library experiences and sources of information used by the new entrants to the Faculty of Management in order to assess whether they have adequate experience in using the school library. The results indicated that all the respondents have been asked by their teachers to read materials other than notes given in the class room. More than 85% confirmed that they used the school library when they were studying for GCE/AL examination and 61% of them visited the school library daily, few days a week or once a week. With regard to library usage, 85% of respondents borrowed books followed by 56% who used the school library as a study place and 44% used the library catalogue. It is remarkable that 98% of students felt that they needed to read books other than the notes given by the teachers. Respondents who used different sources of information other than the school library were asked to mention from where they got them. Of the respondents, 73% purchased from bookshops and borrowed from friends or relatives and 81% of them mentioned that the tuition class provided needed materials as handouts. Results further revealed that the majority (54.3%) did not have access to social media but half of them had email accounts and more than 58% was willing to communicate with the library digitally. The results of this study can be used when planning library instructional programs for the undergraduates
Keywords: University New Entrants, School Library Use, User Assessment, Information Sources